Carta de Direitos das Bibliotecas Escolares e outras Unidades Documentais nas Escolas Portuguesas - BAD, Cadernos (1996)
Carta de Direitos das Bibliotecas Escolares e outras Unidades Documentais nas Escolas Portuguesas